Menumbuhkan Minat Baca Siswa Melalui Pemanfaatan Pojok Baca Di Kelurahan Tomuan - Krisdayanti Riana Lumban Gaol; Febru Siregar; Fernando Fernando; Cares Hutabarat; Seferlina Buulolo; Ruslan Juliana Pardosi (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This community service program aims to increase children's interest in reading in Tomuan Village, East Siantar District, Pematangsiantar City, through the establishment of a reading corner. This service uses methods that include preparation, implementation and evaluation. The results of the service show that the reading corner received a positive response from the community, with an increase in children's interest in reading, especially towards picture books and short stories. Children who were initially shy became more enthusiastic and began to explore the various books available. The reading corner is also a means of socialization, where children share stories and interact with each other. In conclusion, this program succeeded in creating a supportive reading environment, improving literacy skills, and forming reading habits from an early age. In this way, it is hoped that the reading corner can produce a generation that is intelligent, responsible and ready to face future challenges.